If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (r + 3)(r + 3)(r + 3)(r + 3) Reorder the terms: 0 = (3 + r)(r + 3)(r + 3)(r + 3) Reorder the terms: 0 = (3 + r)(3 + r)(r + 3)(r + 3) Reorder the terms: 0 = (3 + r)(3 + r)(3 + r)(r + 3) Reorder the terms: 0 = (3 + r)(3 + r)(3 + r)(3 + r) Multiply (3 + r) * (3 + r) 0 = (3(3 + r) + r(3 + r))(3 + r)(3 + r) 0 = ((3 * 3 + r * 3) + r(3 + r))(3 + r)(3 + r) 0 = ((9 + 3r) + r(3 + r))(3 + r)(3 + r) 0 = (9 + 3r + (3 * r + r * r))(3 + r)(3 + r) 0 = (9 + 3r + (3r + r2))(3 + r)(3 + r) Combine like terms: 3r + 3r = 6r 0 = (9 + 6r + r2)(3 + r)(3 + r) Multiply (9 + 6r + r2) * (3 + r) 0 = (9(3 + r) + 6r * (3 + r) + r2(3 + r))(3 + r) 0 = ((3 * 9 + r * 9) + 6r * (3 + r) + r2(3 + r))(3 + r) 0 = ((27 + 9r) + 6r * (3 + r) + r2(3 + r))(3 + r) 0 = (27 + 9r + (3 * 6r + r * 6r) + r2(3 + r))(3 + r) 0 = (27 + 9r + (18r + 6r2) + r2(3 + r))(3 + r) 0 = (27 + 9r + 18r + 6r2 + (3 * r2 + r * r2))(3 + r) 0 = (27 + 9r + 18r + 6r2 + (3r2 + r3))(3 + r) Combine like terms: 9r + 18r = 27r 0 = (27 + 27r + 6r2 + 3r2 + r3)(3 + r) Combine like terms: 6r2 + 3r2 = 9r2 0 = (27 + 27r + 9r2 + r3)(3 + r) Multiply (27 + 27r + 9r2 + r3) * (3 + r) 0 = (27(3 + r) + 27r * (3 + r) + 9r2 * (3 + r) + r3(3 + r)) 0 = ((3 * 27 + r * 27) + 27r * (3 + r) + 9r2 * (3 + r) + r3(3 + r)) 0 = ((81 + 27r) + 27r * (3 + r) + 9r2 * (3 + r) + r3(3 + r)) 0 = (81 + 27r + (3 * 27r + r * 27r) + 9r2 * (3 + r) + r3(3 + r)) 0 = (81 + 27r + (81r + 27r2) + 9r2 * (3 + r) + r3(3 + r)) 0 = (81 + 27r + 81r + 27r2 + (3 * 9r2 + r * 9r2) + r3(3 + r)) 0 = (81 + 27r + 81r + 27r2 + (27r2 + 9r3) + r3(3 + r)) 0 = (81 + 27r + 81r + 27r2 + 27r2 + 9r3 + (3 * r3 + r * r3)) 0 = (81 + 27r + 81r + 27r2 + 27r2 + 9r3 + (3r3 + r4)) Combine like terms: 27r + 81r = 108r 0 = (81 + 108r + 27r2 + 27r2 + 9r3 + 3r3 + r4) Combine like terms: 27r2 + 27r2 = 54r2 0 = (81 + 108r + 54r2 + 9r3 + 3r3 + r4) Combine like terms: 9r3 + 3r3 = 12r3 0 = (81 + 108r + 54r2 + 12r3 + r4) Solving 0 = 81 + 108r + 54r2 + 12r3 + r4 Solving for variable 'r'. Combine like terms: 0 + -81 = -81 -81 + -108r + -54r2 + -12r3 + -1r4 = 81 + 108r + 54r2 + 12r3 + r4 + -81 + -108r + -54r2 + -12r3 + -1r4 Reorder the terms: -81 + -108r + -54r2 + -12r3 + -1r4 = 81 + -81 + 108r + -108r + 54r2 + -54r2 + 12r3 + -12r3 + r4 + -1r4 Combine like terms: 81 + -81 = 0 -81 + -108r + -54r2 + -12r3 + -1r4 = 0 + 108r + -108r + 54r2 + -54r2 + 12r3 + -12r3 + r4 + -1r4 -81 + -108r + -54r2 + -12r3 + -1r4 = 108r + -108r + 54r2 + -54r2 + 12r3 + -12r3 + r4 + -1r4 Combine like terms: 108r + -108r = 0 -81 + -108r + -54r2 + -12r3 + -1r4 = 0 + 54r2 + -54r2 + 12r3 + -12r3 + r4 + -1r4 -81 + -108r + -54r2 + -12r3 + -1r4 = 54r2 + -54r2 + 12r3 + -12r3 + r4 + -1r4 Combine like terms: 54r2 + -54r2 = 0 -81 + -108r + -54r2 + -12r3 + -1r4 = 0 + 12r3 + -12r3 + r4 + -1r4 -81 + -108r + -54r2 + -12r3 + -1r4 = 12r3 + -12r3 + r4 + -1r4 Combine like terms: 12r3 + -12r3 = 0 -81 + -108r + -54r2 + -12r3 + -1r4 = 0 + r4 + -1r4 -81 + -108r + -54r2 + -12r3 + -1r4 = r4 + -1r4 Combine like terms: r4 + -1r4 = 0 -81 + -108r + -54r2 + -12r3 + -1r4 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(81 + 108r + 54r2 + 12r3 + r4) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(81 + 108r + 54r2 + 12r3 + r4)' equal to zero and attempt to solve: Simplifying 81 + 108r + 54r2 + 12r3 + r4 = 0 Solving 81 + 108r + 54r2 + 12r3 + r4 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4*60-2*60= | | 4x-2*(60)+2x-(60)=180 | | 0=(z-3)(z-3)(z-3) | | 5p+3=14 | | (x-6)(x-4)=-16 | | 4x-2*(-60)+2x-(-60)=180 | | 0=[(2m+7)-n][(2m+7)-n] | | 0=9/16y-63 | | 4*0-2y+2*0-y=180 | | x^2+4x+y^2+6y=-13 | | 0=[(9r-s)+2][(9r-s)-2] | | 4*(30+0.5y)-2y+2*(30+0.5y)-y=180 | | n=4(3+2) | | 0=[(4y-1)+z][(4y-1)+z] | | 2.44-3.1t=21.05 | | 80t=720 | | 90t=720 | | 0=(2z^4-3y)(2z^4-3y) | | 36+0+4*36-2*0+2*36-0= | | 5ln(6x)=40 | | 3/5x-4/7y-2x+5/7y | | 0=(a-6b)(a-6b) | | 4x+8+6x-5=33 | | x+0+4x-2*0=180 | | 13+3p+10=23+3p | | 36+0.2y+4*(36+0.2y)-2y=180 | | 5(2c+7)-3c=7(c+5) | | 7+4y=39 | | 3x+7=9x+1 | | 2m-(5m-4)=7+(-m+2) | | x/4+9=15 | | 7n+3=2n+23 |